Do Power-Sharing Systems Behave Differently amid Regional Uprisings? - Fakhoury, Tamirace (2014)
This article examines Lebanon’s political dynamics in the context of the 2011 Arab protest wave, and seeks to integrate events in the small republic within the broader literature written on the contagion effects of the uprisings. It argues that the uprisings’ trajectories provide a terrain to better understand Lebanon’s politics of sectarianism and their interactions with the region’s upheavals. The article focuses on analyzing how power-sharing along sectarian lines exacerbates conflict while hampering collective action and democratic advances.